Adolescents’ attitudes towards healthy eating: A scale development study - Remzi Eşkil; Kezban Gülşen Eşkil; İmdat Yarım (PLoS ONE, 2025)
The aim of this study is to develop a measurement tool that can reliably and validly measure adolescent individuals’ attitudes toward healthy eating. The study group consisted of 1,006 individuals, including 495 males and 511 females, aged between 11 and 17 years. In this study, an exploratory sequential design was applied. A semi-structured interview form was used to create the item pool, and compositions were written. The “Davis Technique” was employed to assess the content validity of the items. For data analysis, SPSS 25.0 was used for EFA and reliability analysis, and Lisrel 8.7 was utilized for CFA. Based on the result of EFA, a structure consisting of 4 factors and 18 items was formed. The total variance explained is 59.05. According to CFA analysis, factor loadings range from .43 to .81, and X2/df = 1.65, RMSEA = .040 were found. Furthermore, the NFI, NNFI, PNFI, CFI, IFI, GFI, AGFI, PGFI, and RFI fit indices were found to be excellent and within the good range. In the analysis of the lower and upper groups of the scale (27%), statistically significant differences were observed in all items (p < .01). To test the reliability of the scale, Cronbach’s Alpha, Spearman-Brown (Split-half), and Guttman Lambda-6 coefficients were examined. The scale sub-dimension correlations ranged from .526 to .129. In conclusion, the developed scale demonstrates that it can validly and reliably measure adolescents’ attitudes toward healthy eating.